TEKNIK PERMAINAN VIOLIN PADA "VIOLIN AND PERCUSSIONS" KARYA IWAN GUNAWAN DALAM PERTUNJUKKAN SMELL OF BLISS - Saviera Ardhita, - (2021)
"Violin and Percussions" is a music art written by Iwan Gunawan, Andre Leine with Harijono Roebana as coreographer, and Liza Ferschtman as solo violinist for Smell Of Bliss show in the Netherlands in 2014. The data was collected using a qualitative descriptive method. This research process using content analysis techniques, seeing the data or documents already owned are in the form scores that can be classified as unstructured data. This study aims to describe the fingering and bowing in the violin playing techniques at "Violin and Percussions" on the B - L - Q - R part. The results of this study has found two main problems that must be solved, that is playing octave intervals and applying contrasting dynamics. To overcome the two problems in the violin playing techniques, the researcher and violinist agreed to slow down the tempo before it becomes 'a tempo' for transitional melodies that have contrasting dynamics. Next, the octave intervals played slowly from prime - sekonde - terz intervals and so on to octaves, so that the composition of the melody can be played according to the composer's desire.